Social health outcomes following thermal injuries: a retrospective matched cohort study. Issue 9 (15th June 2009) - James-Ellison, M; Barnes, P; Maddocks, A; Wareham, K; Drew, P; Dickson, W; Lyons, R A; Hutchings, H
Abstract : Introduction: Over 50% of children admitted with burns are aged under 3 years. US studies suggest that up to 26% of childhood burns are non-accidental, although UK reports are lower (1–16%). Objectives: To determine the social health outcomes of burned children as regards the number of children abused, neglected or "in need" before the age of 6 years compared with matched controls. Methods: A retrospective matched cohort study. 145 children aged under 3 years admitted for burns in 1994–1997 were matched with controls for sex, age and enumeration district and followed up until 2003. Electronic routine databases provided study data on local authority care episodes and Social Services referrals by age 6 years. Results: 89.0% of cases had accidental burns and four cases (2.8%) had non-accidental burns. No case was attributed to neglect. By their sixth birthday cases were statistically more likely to have been referred to Social Services with 14 (9.7%) of the burned children having been abused or neglected versus two (1.4%) controls (95% CI 0.030 to 0.13, p = 0.004). Forty six (32%) cases versus 26 (18%) controls were defined as "in need" (95% CI 0.047 to 0.23, p = 0.006). Conclusion: Although most burns were deemed accidental, 2.8% were categorised as non-accidental at presentation. Almost a third of the burned children went on to be "in need". Children with a burn appear to be at higher risk of further abuse or neglect compared with controls. A burn therefore could be a surrogate marker indicating need for closer supervision and follow-up by professionals.